In mixed company : - Rothwell, J. Dan (Harcourt Brace, 1995)
Designed for courses involving Small Group Communication discussions, the acclaimed IN MIXED COMPANY thoroughly addresses the theme of communication in small groups. The author has preserved the essence that made previous editions so popular and has expanded the central unifying theme that says cooperation in small groups is usually superior to competition. The communication competence model continues to guide discussions of key small group concepts and processes. Systems theory also remains as a key theoretical component of the text and finally, an extensive discussion and analysis of power in small groups continues to separate IN MIXED COMPANY from other textbooks.